Apolipoprotein(a) Antisense Oligonucleotides: A New Treatment Option for Lowering Elevated Lipoprotein(a)? - Schreml, Julia; Gouni-Berthold, Ioanna (Current Pharmaceutical Design, 2017)
Background: Lipoprotein(a) [Lp(a)] is a particle similar to LDL that contains an additional protein called apolipoprotein(a) [apo(a)]. Recent epidemiologic and Mendelian randomization studies have provided evidence that Lp(a) may be causally related to the pathogenesis of atherosclerosis and cardiovascular disease (CVD). While the risk association between Lp(a) concentrations and CVD is weak it seems to be continuous in shape and without an obvious threshold for Lp(a) levels. Methods: Circulating concentrations of Lp(a) are genetically determined and desirable levels are < 50 mg/dl. A plasma concentration of 60 mg/dl is associated with an odds ratio for coronary heart disease of about 1.5 after adjustment for other cardiovascular risk factors. Results: Extended-release niacin is the pharmacologic means of choice for decreasing elevated Lp(a) levels by 20-30% but it is often poorly tolerated due to adverse reactions. Diet, exercise and lipid-lowering drugs such as statins, fibrates and ezetimibe are without effect. In patients with severe progressive CVD and very high Lp(a) levels, lipoprotein apheresis may be used to decrease Lp(a) concentrations. However, it is an expensive and impractical treatment for most patients and its feasibility depends on the healthcare reimbursement system of the respective country. Since no established treatment reduces Lp(a) without influencing other lipoproteins, there has been no trial examining whether decreasing Lp(a) concentrations translates to clinical benefits. Conclusion: Recently, an antisense oligonucleotide against apo(a), IONIS-APO(a)Rx, has been shown to selectively decrease Lp(a) by 80%. A phase 2 study with this drug has been completed in late 2015 and results are expected to be published soon.
Keywords: Antisense oligonucleotide